The Disruptions-Related Tuberculosis Case Finding and Treatment in Indonesia during COVID-19 - Unicha, Mutiara Shinta Noviar; Dwi Murdiati; Intan Wahyuni Tukiyo; Intan Pristian Yuliyani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2023)
Background: This study aims to find out the disruptions related to the TB new case finding and treatment program during the COVID-19 pandemic in Indonesia. This understanding is needed to conceive effective strategies to face and prevent the issues of TB program implementation in health services and health care. Methods: This review used selected articles conducted in Indonesia, published during the COVID-19 pandemic from March 2020 to July 2022 from ScienceDirect, PubMed, ProQuest, and Google Scholar journal databases. Results: 7187 related studies were identified by the keywords. In the final process, there were 7 studies included in the review. The studies covered 5 provinces mentioned 3 cities and 2 regencies. The disruptions in TB new case finding and treatment health services were affected by participants' knowledge of the differences between TB and COVID-19, family support, family history of COVID-19, comorbidity, double workloads of the health workers, and accessibility of healthcare accommodation. New methods for new case findings and treatment adherence such as scheduled home visits, community-based finding health empowerment, the development of a new invention of eNose-TB, modification of the administration process, and the use of virtual care were implemented to overcome these issues during this pandemic. Conclusion: The majority of tuberculosis issues during COVID-19 were related to social determinants. The health empowerment that involved community and several modifications to health services were applied to healthcare as resolutions besides preserving the achievement of new case findings and treatment programs.